Selling a story: a survey investigating the willingness of consumers in the Midwest to acquire specialty crops viewed in an online environment - Jones, Ernest Francis (Kansas State University, 2020)
The underpinning of this work is focused on small-scale family-operated farms of specialty crops within the U.S. Midwestern region. The Midwestern region, encompassing the states of: Illinois, Indiana, Iowa, Kansas, Michigan, Minnesota, Missouri, Nebraska, North Dakota, Ohio, South Dakota and Wisconsin was selected for this study, in part, because of the concentration of specialty crop growers which represent an important and diverse industry. For instance, the value of domestically grown tree nuts, citrus, and noncitrus fruits has increased from $9.1 billion in 1995 to $30.6 billion in 2017. Against this backdrop, the aim of this research is to explore if the manipulation of narratives and or storytelling, prices, and logistics can influence consumers’ willingness to purchase specialty crops viewed in an online environment. Many small-scale family-farms promote their agricultural produce locally to prospective buyers. The types of promotion vary from farm to farm but typically include farmer markets, stores selling locally-grown food and garden centers. Additionally, the local-food movement has redirected consumers’ interest toward agricultural produce emerging from small-scale family-farms. The shift in consumers’ interest can be attributed in part to heightened public concerns with food security at the community level, environmental impact associated with the distribution of food, and perceptions of large agricultural entities. The foregoing concerns have motivated many consumers to acquire cognizance of the origin of their food with the ultimate aim of patronizing local farmers. The aim of this study is to investigate the facets that persuade consumers to purchase specialty crops hinged upon what is observed online. Against this backdrop, this study will embrace the variables of storytelling/narrative, travel distance, door-to-door delivery, and price to explore consumers’ interest to acquire specialty crops. This study referenced the elaboration likelihood model, as persuasive communication is an acknowledged element in selling efforts. This work reviewed literature pertaining to credible sources and how credible sources can contribute to the profitability of selling specialty crops online. The review also included framing messages with an emotional appeal which are best suited for an audience with little or no knowledge of specialty crops. Results indicate that there is interest among consumers to acquire specialty crops viewed in an online environment, as 85.6% of respondents chose to purchase over not purchasing specialty crops. In particular, this study revealed that consumers are willing to have specialty crops delivered door-to-door within the price intervals of $15 to $17.50 for eight to twelve pounds of seasonal local produce–with an additional fixed-delivery fee of $5.00. Although a price of $20.00 resulted in a lesser degree of interest. Also, growers should target technologically savvy consumers comfortable with being online.
Keywords: Specialty crops; e-commerce